The effects of spinal neddle on skin puncture pain during spinal anesthesia for caesarian sections: Comparison of 26G Quincke and 26G atraumatic spinal needles (Annals of Medical Research, 2021)
None
Keywords: Skin Puncture Pain; Spinal Anesthesia; Spinal Needle; Caesarian Sections.br /